Fast-track and regular teacher training programs in special education - Henson, Janice L. (2009)
This is a qualitative study about the regular and fast-track teacher training programs in Special Education. It aimed to identify the different curricula of the teacher training programs and how they were conducted in selected institutions in Metro Manila. This research also compared the graduates of these non-degress courses from their counterparts in the degree programs of different colleges and universities. It provided data on the performance and competencies of the teachers in the field and assessed the curriculum components of the said programs. The data showed that the graduates of regular teacher training programs in Special Education perform better in the field and are more satisfied in terms of how their training and education was handled than their counterparts in the fast-track programs.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Special education teachers -- Training of -- philippines -- Manila Metropolitan Area; Special education -- Philippines -- Manila Metropolitan Area